OVERVIEW OF THE IMPORTANCE AND FUNCTIONS OF THE PSYCHOLOGICAL SERVICE - Abdurashid Abdumannobovich Turgunov; Abdumannobova Mubinabonu Abdurashid Qizi (American Journals Publishing, 2023)
Psychological service is an integral part of modern life and has become increasingly important in recent years due to the growing recognition of the importance of human mental health. This article provides an overview of the role and functions of the psychological service, including assessment, diagnosis, treatment and prevention of mental disorders. Also, the article highlights the history of the psychological service and the need to increase resources to support the provision of high-quality psychological services, especially in light of the growing demand for mental health services worldwide.
Keywords: psychological service, counseling, diagnostics, therapy, test, methodology, psychological technique, cognitive functioning, emotional functioning, research.